Cycle time improvement by lean Six Sigma for the Cutting Tool Production Line / Muhammad Syahmi Shahar and Noor Azlina Mohd Salleh - Shahar,, Muhammad Syahmi; Mohd Salleh, Noor Azlina (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
A cutting tool manufacturing company in Malaysia is facing challenges in fulfilling demand of cutting tool throughout the distribution line. With the rising orders from different countries, the cutting tool manufacturer is trying to improve their production line by reducing cycle time without high value expenditure. This research paper presents an implementation of Lean Six Sigma approach at a cutting tool manufacturing company in Malaysia. The main function of lean six sigma approach is for continuous improvement on the output quality, reducing defects, minimizing waste and minimizing cost in production. With the main objective of reducing cycle time at polishing section, a case study was conducted at the cutting tool manufacturing company in Klang, Selangor, Malaysia. The methodology used for this study is DMAIC which refers to Define, Measure, Analyze, Improve and Control. With the approach of DMAIC, the Polishing section has undergone the cycle time improvement for higher yield in production. Results shows that, with proper implementation, Lean Six Sigma could help in cycle time improvement and problem identification. This research may also help in further development towards the cycle time improvement system for machining oriented manufacturing companies.